BUSINESS PERFORMANCE OF MUSLIM ENTREPRENEURS: MASLAHAH SCORECARD PERSPECTIVE - Mugni Fadil Romdhoni; Juliana Juliana; Hilda Monoarfa (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2022)
This research is based on some of scientists who mention that religious values can’t determine performance and in general and Muslims generally has low achievement. This research aims to find out the big picture of business performance of Muslims entrepreneurs, indicator that influences business performance of Muslims entrepreneurs the most and also the difference between business performance of overseas Muslims entrepreneurs and local Muslims entrepreneurs. The population of this research are Minangkabau Muslim entrepreneurs and Local Muslim entrepreneurs in Cirebon. Sampling technique that is used in this research is purposive sampling - quota sampling with total sample of 60 Muslim entrepreneurs that are divided into 3 areas; fotocopy/office stationery, fashion and culinary. Method that is used in this research is descriptive with a quantitative approach. Data analysis techniques that is used in this research are measuring tools Maslahah ScoreCard. The result of this research shows that these two ethnic have carried out business performances which have matched with the syariah with enough performance score in both process performance and results performance. Minangkabau muslim entrepreneurs have process performance 0,679 and 0,663 for the local muslim entrepreneurs. While in performance results, both get a performance score of 1 or have implemented benefits of all sizes. Although the performance results get full value in the implementation, but the achievement of every targets of Minangkabau Muslim entrepreneurs and local entrepreneurs in Cirebon City is still not optimal.